Comparing Constraints to Economic Stabilization in Macedonia and Slovakia : Macro Estimates with Micro Narratives - Melecky, Martin; Najdov, Evgenij (World Bank, Washington, DC, 2012)
This paper re-emphasizes the link from structural policies to enhanced macroeconomic stabilization using a small structural model estimated on quarterly data for Macedonia and Slovakia over 1995-2007. The success of macroeconomic stabilization, typically in the hands of monetary policy, is not only determined by a suitable choice of the nominal anchor, which shapes the reaction function of monetary policy, but also the constraints within which the monetary policy strives to achieve its objectives. The key attributes of the constraints to macroeconomic stabilization are economic rigidities and structural shocks. By benchmarking the estimated economic rigidities and structural shocks faced by Macedonia to those faced by Slovakia, the authors find that Macedonia has relatively weaker transmission mechanisms of monetary policy, higher output rigidity, and a lower exchange rate pass-through, and faces larger external shocks. For Macedonia, these relatively higher constraints on monetary policy together with the chosen exchange rate anchor result in greater output and inflation volatility relative to Slovakia. Hence, it appears that small, open economies with stronger economic rigidities should apply monetary policy regimes that allow for more flexible adjustments in external relative prices to enhance their macroeconomic stability.